Physical activity and its impact on academic achievement among health sciences students Universiti Kebangsaan Malaysia - Nur Najmi Mohamad Anuar; Faten Najjah Tuan Hussain; Anis Atiqah Sobri; Narissa Hairani Hamidon; Syamiemy A’riffah Mohd Nasir; Nurul Nabilah Mohd Zulfakarudin; Nursyamimi Rasmadi; Norsyafiqah Mohd Hidzir; Azman Abd Karim; Fazzreena Mohd Nazir; Syahir Haziq Ibrahim; Izatus Shima Taib (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2020)
Self-determination influences physical activity which improves student’s health status leading to an increase in their academic achievements. However, these relationships among health sciences students remain unclear. Therefore, this study aims to investigate the influences of self-determination towards physical activity and the relationship between physical activity level and academic achievement among third-year students of Faculty of Health Sciences, Universiti Kebangsaan Malaysia (UKM). A cross-sectional study was conducted among 180 third-year students from all programs in Faculty of Health Sciences, UKM from March to May 2020 using a self-administered short-form version of the International Physical Activity Questionnaire (IPAQ-SF) and the third version of the Behavioural Regulation in Exercise Questionnaire (BREQ-3). The Kruskal Wallis test was done to evaluate the relative autonomy index (RAI) and Metabolic Equivalent Task (MET) among groups, while a simple linear regression was performed to identify the relationship between self-determination and physical activity levels and between physical activity levels and academic achievements. A significant difference of self-determination level was found between light and a moderate level of physical activity (p<0.05) and between light and vigorous level of physical activity (p<0.001). Our findings also revealed that a positive moderate relationship was found between the level of physical activity and self-determination level (R= 0.248, R2 =0.062) where self-determination level significantly predicts the physical activity performed (p<0.01). However, a low negative relationship was found between the level of physical activity and academic achievement (R= 0.123, R2 =0.015). In conclusion, self-determination plays a key role in contributing the physical activity levels, while the physical activity did not influence the academic achievement among the third-year students of Faculty of Health Sciences, Universiti Kebangsaan Malaysia.